KEDUDUKAN ANAK LUAR KAWIN DALAM PERSPEKTIF HUKUM DI INDONESIA - Tri Wuryaningsih; Eti Mul Erowati; Soebyanto Soebyanto2 (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2024)
ndonesia is still faced with the issue of unwanted pregnancies and children born out of wedlock (out-of-wedlock children) which continues to increase from time to time. This problem requires serious attention regarding the rights and future of illegitimate children. In Positive Law in Indonesia, illegitimate children have different civil positions and rights, so the problem in this research is, what is the position of illegitimate children in the Civil Code, Law Number 1 of 1974 concerning Marriage and Decisions? MK Number 46/PUUVIII/2010 and how to protect children in the legal practice space, especially in the Religious Courts. This research uses a normative juridical approach with descriptive research specifications. The data source used is secondary data, then the analysis of the results will be presented in narrative form and written systematically with qualitative normative data analysis